REVIEW OF ISLAMIC LAW ON THE PRACTICE OF PROFIT SHARING ON GOAT LIVESTOCK - Widyani, Retno (Hukum Responsif, 2025)
The business that has endured since the time of Prophet Adam until the end of time is goat farming. The business model is based on a profit-sharing system between investors and managers. This study aims to analyze the Islamic legal perspective on profit-sharing practices in goat farming. The research was conducted with a qualitative approach through literature review. The results of the study are as follows: (1) From an Islamic legal perspective, the profit-sharing practice in goat farming has not fully complied with the applicable regulations. The agreement between shahibul maal and mudharib is often verbal rather than written, which contradicts the provisions in Q.S. Al-Baqarah/2: 282. This could lead to potential disputes between shahibul maal and mudharib in the future; (2) In practice, shahibul maal often violates the agreement with mudharib, citing urgent needs that require the cancellation of the mudharabah. As a result, the compensation given to the mudharib is usually not equivalent to the value of the goat kids that should have been received.